The role of anthropometric, performance and psychological attributes in predicting selection into an elite development programme in older adolescent rugby league players - Tredrea, M.; Dascombe, B.; Sanctuary, C. E.; Scanlan, A. T. (Journal of Sports Sciences, 2017)
This study aimed to identify attributes that discriminate selected from non-selected players and predict selection into a rugby league development programme in older adolescent players. Anthropometric, performance and psychological attributes were measured in under-16 (N = 100) and under-18 (N = 60) rugby league players trialling for selection into a development programme with a professional Australian club. Sprint times (P < 0.001), predicted VO2max (P = 0.002) and push-ups1 min (P = 0.004) were superior in selected under-16 players, and sprint times (P = 0.045), push-ups1 min (P < 0.001) and chin-ups1 min (P = 0.013) were superior in selected under-18 players. Further, 10-m sprint (ß = -7.706, standard error [SE] = 2.412), VO2max (ß = 0.168, SE = 0.052) and body mass (ß = 0.071, SE = 0.023) significantly predicted selection (R2 = 0.339) in under-16 players, while push-ups1 min (ß = 0.564, SE = 0.250), 10-m sprint (ß = -68.477, SE = 28.107), body mass (ß = 0.360, SE = 0.155) and chronological age (ß = -3.577, SE = 1.720) significantly predicted selection (R2 = 0.894) in under-18 players. These findings emphasise the importance of performance attributes in junior rugby league and indicate talent identification test batteries should be age-specific in older adolescent players.